Standard method of test for breaking strength and elongation of cotton fibres (flat bundle method)1
The flat bundle test for cotton fiber strength gained immediate acceptance after its introduction in 1953. The first successful instrument was an inclined plane device with the beam calibrated in pounds. The specimen was clamped with no space between the jaws and was called zero-gauge strength. Results were expressed in Pressley Index (P.I.)calculated as the force-to-break in pounds divided by the bundle weight in mg. Obviously, P.I. is not a standard engineering unit.
Keywords: BREAKING; ELONGATION; BREAKING; STRENGTH; BUNDLE STRENGTH; COTTON; FIBRE BUNDLE TESTING; FIBRES; STANDARDS; TENSILE TESTING; USA